Impact of conflict management styles and emotional intelligence on job performance among construction employees in Selangor and Kuala Lumpur, Malaysia - Nik Mohamed Sahabuddin @ Nik Muhamad, Nik Hasnini (2017)
The purpose of the present research is to investigate the relationships between conflict management styles (CMSs) and job performance (JP). The moderating role of emotional intelligence (EI) on the relationship between predictors and job performance was also investigated. Organizations the world over today have moved through complex changes, witnessing a number of transformations, rapid revolutions, and challenges, especially within an organization’s strategy, structure, practice and paradigm. Such challenges happen in Malaysia too, including in the construction industry which contributes to the Malaysian economy and infrastructure development of the country. The nature of the construction industry is vulnerable and sensitive. The employees play a crucial role in gaining competitive advantage for the industry and need to demonstrate high job performance to achieve this. The present study used a survey design to achieve its objectives. Simple random sampling was employed in this study. A total of 200 usable questionnaires were obtained from selected construction companies in Selangor and Wilayah Persekutuan Kuala Lumpur. The Structural Equation Modelling (SEM) technique was used for data analysis. The findings revealed that there is a significant relationship between employees CMS and JP. Therefore it is concluded that employee’s conflict management styles affect their job performance. This study indicated that the construction employees seem to be employing the “positive” style of conflict management which are integrating, compromising and obliging. This is an important finding that CMS practices are found to be crucial and related to increase employees’ job performance. This study also confirms that EI moderates the relationship between CMS and JP. The presence of emotional intelligence would strengthen the relationship between CMS practices and employee job performance. Finally, it is suggested that the organization must adopt effective CMS and to develop employees EI to improve employees JP the of the organization. Training programs on conflict management and emotional intelligence are needed to improve their job performance.